Proven skills the new yardstick for schools. - Bell, T.E.
Under its new rules, the Accreditation Board for Engineering and Technology's (ABET) Engineering Criteria 2000 (EC 2000) will focus on the results of an engineering education, rather than on the curriculum. As of September 2001, when the document becomes mandatory, EC 2000 will emphasize instead the learned abilities an engineer should possess upon entering into professional practice. With this simple, yet radical, change in focus from input to outcome, EC 2000 aims to get faculties to overhaul their teaching methods and curricula. The criteria are even sparking international educational reform. Many non-US institutions want their programs awarded the status of ?substantial equivalency? to US programs, so their graduates can more realistically aspire to jobs anywhere in the world. In formulating the novel criteria, ABET, a nonprofit organization, based in Baltimore, Md., did not go it alone. It had the cooperation of academia, industry, and 29 professional engineering societies, including the IEEE
Keywords: Accreditation Board for Engineering and Technology; Engineering Criteria 2000.; Engineering education; International educational reform; Learned abilities; Teaching methods